Planning for uncertainty: proceedings of the 14th annual South Platte forum - Brown, Jennifer, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2003)
Abstracts only of papers presented at Planning for uncertainty: proceedings of the 14th annual South Platte forum held on October 22-23, 2003 in Longmont, Colorado.
October 2003.
Keywords: Watershed management -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water -- Law and legislation -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water use -- South Platte River Valley (Colo. and Neb.) -- Congresses; Droughts -- South Platte River Valley (Colo. and Neb.) -- Congresses